Athletic Ticket Pricing in the Collegiate Environment: An Agenda for Research - Morehead, Craig A.; Shapiro, Stephen L.; Madden, Timothy M.; Reams, Lamar; McEvoy, Chad D. (Journal of Intercollegiate Sport, 2017)
As pressure mounts for intercollegiate athletic departments to be more selfsufficient, administrators must respond by increasing generated revenues. Despite the importance of ticket sales in this endeavor, however, little is known about the underlying ticket pricing structures and policies used by National Collegiate Athletic Association (NCAA) institutions. Of the limited existing scholarship focused on managerial pricing decisions in the field of sport management, only professional sports settings have been addressed. Given the unique operational differences between professional and intercollegiate sport, this paper is designed to establish a foundation from which to build future research concerning the pricing of college sport tickets. The frameworks of stakeholder theory and institutional theory are proposed to ground future study in an attempt to strengthen our understanding of the process and behavior of price setting in intercollegiate athletics.